Potential mechanisms underlying impaired left ventricular function in atrial fibrillation: insights from multi-parametric cardiac magnetic resonance - Wijesurendra, R (2017)
Atrial fibrillation (AF) is the most common sustained arrhythmia and is associated with significant cardiovascular complications, including stroke, myocardial infarction, heart failure, and premature death. The presence of subtle left ventricular (LV) dysfunction is increasingly recognised in patients with AF, raising questions regarding the underlying pathophysiology and potential treatment strategies. I used advanced and multiparametric cardiac magnetic resonance (CMR) methods to investigate potential mechanisms that could contribute to LV dysfunction in patients with AF, controlled ventricular rate and no significant cardiovascular comorbidities (i.e., with so-called “lone” AF). Patients were evaluated before and after catheter ablation, allowing examination of the effect of restoration of sinus rhythm and reduction in AF burden on LV structure, function, energetics, tissue characteristics, and perfusion. I demonstrated for the first time that patents with lone AF before ablation have significantly impaired ventricular energetics and a subtle reduction in LV systolic function compared to control subjects in sinus rhythm. Furthermore, there was only modest improvement (but not normalisation) in LV function following successful ablation, and myocardial energetics remained impaired despite a significant and sustained reduction in AF burden. These findings imply that lone AF may actually be the consequence (rather than the cause) of an underlying cardiomyopathy. Next, to interrogate advanced ventricular tissue characteristics (such as diffuse myocardial fibrosis) in patients with tachyarrhythmia, I developed a novel CMR method involving a systolic readout T1-mapping sequence. Methodological work in volunteers and patients with tachyarrhythmia demonstrated that this method reports clinically equivalent T1 values to the conventional diastolic readout in healthy volunteers, and was feasible in tachyarrhythmia, producing excellent quality T1 maps. When applied to the investigation of patients with AF, I demonstrated that subtle LV dysfunction in lone AF occurs in the absence of CMR evidence of diffuse myocardial fibrosis, suggesting that LV dysfunction may be reversible with appropriate and targeted therapeutic strategies initiated prior to the development of structural LV remodelling. Finally, I used quantitative perfusion imaging to determine absolute myocardial blood flow and coronary reserve in patients with AF, and determine whether microvascular coronary dysfunction could underlie impaired LV function and energetics in patients with AF. I found that myocardial perfusion is significantly reduced in patients with AF in the absence of significant epicardial coronary artery disease, both at baseline and under conditions of vasodilator stress. Lower baseline blood flow was related to reduced LV performance, and there was no significant change in perfusion after successful AF ablation. These novel findings indicate that coronary microvascular dysfunction may be an important pathophysiological mechanism in lone AF, and at least partially responsible for LV dysfunction. Overall, the findings reported in this thesis have potentially far-reaching implications for the management of patients with AF. They suggest that approaches that predominantly target rhythm control (including anti-arrhythmic medications and ablation) are insufficient to normalise the systemic and cardiometabolic phenotype in patients with AF. Further studies are needed to investigate whether novel approaches that target microvascular and energetic dysfunction in patients with AF can contribute to durable restoration of sinus rhythm and improve clinical outcomes.